Ambivalent Attitudes of Islamic Boarding School Alumni Toward Arabic as a Religious Symbol and Communication Tool - 'Amaliah, Thariqatul; Zalila, Nur; Yuniarti, Lita; Salsabila, Sarah; Fahri, Naufal Ario (Study Program of Arabic Language Teaching, 2025)
This study aims to critically explore alumni’s attitudes towards Arabic in the post-boarding context. This research is situated explicitly in Aceh, involving alumni from Ruhul Islam Anak Bangsa, Aceh Besar, as representatives of an Islamic educational environment with strong religious and cultural characteristics. The research method used is a descriptive qualitative case study Design. The study relies on primary data obtained from purposively selected key informants to elicit in-depth experiential narratives. Data were collected through observation, semi-structured interviews, and open-ended questionnaires distributed to boarding alums with diverse professional backgrounds. The data analysis followed a thematic analysis framework, including stages of in-depth Reading, coding, thematic categorization, and interpretation grounded in the conceptual frameworks of ambivalence and language ideology. The results of the data analysis showed that the alumni recognized Arabic as an essential communication tool. Still, its use was limited to specific environments and did not continue actively after leaving the boarding environment. This study highlights the need for a sustainable learning approach and a community of practice that can maintain Arabic as a means of living communication.